Advances in understanding and treating diabetic kidney disease: focus on tubulointerstitial inflammation mechanisms - Xu, Chengren; Ha, Xiaowen; Yang, Shufen; Tian, Xuefei; Jiang, Hong (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD) is a serious complication of diabetes that can lead to end-stage kidney disease. Despite its significant impact, most research has concentrated on the glomerulus, with little attention paid to the tubulointerstitial region, which accounts for the majority of the kidney volume. DKD's tubulointerstitial lesions are characterized by inflammation, fibrosis, and loss of kidney function, and recent studies indicate that these lesions may occur earlier than glomerular lesions. Evidence has shown that inflammatory mechanisms in the tubulointerstitium play a critical role in the development and progression of these lesions. Apart from the renin-angiotensin-aldosterone blockade, Sodium-Glucose Linked Transporter-2(SGLT-2) inhibitors and new types of mineralocorticoid receptor antagonists have emerged as effective ways to treat DKD. Moreover, researchers have proposed potential targeted therapies, such as inhibiting pro-inflammatory cytokines and modulating T cells and macrophages, among others. These therapies have demonstrated promising results in preclinical studies and clinical trials, suggesting their potential to treat DKD-induced tubulointerstitial lesions effectively. Understanding the immune-inflammatory mechanisms underlying DKD-induced tubulointerstitial lesions and developing targeted therapies could significantly improve the treatment and management of DKD. This review summarizes the latest advances in this field, highlighting the importance of focusing on tubulointerstitial inflammation mechanisms to improve DKD outcomes.